Pengaruh Karakteristik Perusahaan dan Corporate Social Responsibility Terhadap Agresivitas Pajak pada Perusahaan Farmasi dan Kosmetika di BEI Tahun 2020-2024 - Ni Luh Putu Krismayanti; I G.A. Desy Arlita (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to examine the influence of firm characteristics and corporate social responsibility on tax aggressiveness among pharmaceutical and cosmetic companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2024. The study was conducted using financial reports from companies in the pharmaceutical and cosmetic sub-sectors; as the subjects are publicly listed issuers, the necessary financial data were accessible via the IDX. The study population consisted of pharmaceutical and cosmetic companies listed on the IDX between 2020 and 2024, with 22 companies recorded in the 2020 IDX annual statistics. A purposive sampling method was employed, resulting in a final sample of 20 companies. Secondary data—specifically the financial reports of listed pharmaceutical and cosmetic companies—were used for this study. Data collection involved secondary data gathering and a literature review. Data processing was performed using SPSS version 26 for Windows. Data analysis included classical assumption tests, multiple linear regression analysis, the F-test, and the t-test. The results indicate that: (1) profitability has a negative and insignificant effect on tax aggressiveness; (2) leverage has a positive and significant effect on tax aggressiveness; (3) audit quality has a positive and insignificant effect on tax aggressiveness; and (4) corporate social responsibility has a positive and insignificant effect on tax aggressiveness.